Problem posing and game invention for Mathematics learning (Edma 0-6: Educación Matemática en la Infancia, 2021)
We present our approach to posing math problems and, within that framework, inventing games. We consider that this integrated approach contributes to stimulating children's mathematical thinking and the development of teachers' didactic-mathematical competences, taking into account the positive emotions generated in children when they create problems and even more when they create games and play their own games. We present four didactic experiences with children, as case studies, and a didactic experience with primary school teachers, developed in a non-face-to-face mode. The experiences showed not only close relationships between inquiry, problem posing and problem solving, but also great emotional involvement, both of children and teachers; thus, we can affirm that they are concrete ways of stimulating, in playful contexts, creativity, intuition and mathematical thinking. The experience with teachers entails a proposal for didactic-mathematical inquiry, applicable, with various mathematical environments, in initial and ongoing teacher training programs.
Keywords: Problem posing; Game invention; Emotions; Inquiry; Teacher training